Improved Criteria for the Design of Microsprinkler Systems to Maximize Crop Profit under Different Water Supply Scenarios - Silva Júnior, Hélio Moreira Da [UNESP]; Saad, João Carlos Cury [UNESP] (American Society of Civil Engineers (ASCE), 2021)
Population growth and increasing food demand require cropping systems that produce higher yields with less water. Microirrigation can fulfill this demand but has a high investment cost, which can be reduced with adequate irrigation design and management. The design is based on pre-established emission uniformity (EU) by combining equipment characteristics and hydraulic configurations. This study evaluated the influence of EU and irrigation depth on the emission uniformity obtained after the design (EUad), yield uniformity, and the expected profit for a microsprinkler-irrigated citrus orchard on sloping terrain for the growing conditions of Leme, Sao Paolo, Brazil. The research was developed under different scenarios of EU values, negative slope gradients in the irrigation subunit, and critical period irrigation depths, resulting in practical guidelines for irrigation practitioners and farmers. To design a system under level conditions, an EU value of 85% is recommended, because the resulting EUad was always higher than the EU value considered at the design stage. For sloping conditions, the EU should be at least 90% in microirrigation subunits, and the higher the slope gradient, the greater the EU must be. Although the microirrigation system design was based on high values of the pre-established EU, the evaluated variation in the EU did not significantly modify the net crop profit. With a water supply, a 50% reduced irrigation depth generated a net profit 16.2% lower than that of the best option but had the highest irrigation water-use efficiency (IWUE) among the studied treatments. To obtain production uniformity and higher profit, not only the irrigation system uniformity but also the irrigation adequacy must be considered when selecting the appropriate water depth to be applied.
Keywords: Citrus; Linear programming; Microirrigation; Productivity